Society and Manner in Joseph Conrad's Victory (Journal of the College of Education for Women, 2019)
In his novel entitled Victory. Joseph Conrad asserts himself as a writer for manas a moral agent in this universe. His characters exhibit the possibilities for isolationand moral deterioration in modern life. The aim of this research is to investigate somesocial issues that touch the core of humanity. In this novel, Conrad's perceptive eyeshas noted so many social issues that need to be tackled. Implicitly and explicitly,Conrad launches so many controversial issues like : communication anddisengagement or skepticism , conflict between heart and mind ,fate, demonicidentification sense of guilt in man, men , women and homosexuality, the clashbetween the civilized and the raw ,the disregarded local people and the disregardedChinese , and finally the issue of gossip in society .